SKRINING UNTUK TOLERANSI TERHADAP STRES KEKERINGAN PADA 36 VARIETAS KEDELAI PADA FASE PERKECAMBAHAN - Wahyu Widoretno (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Water stress due to drought is the most significant abiotic factor limiting crop growth and development. Drought stress inhibit germination and seedling growth, and extention of inhibition in germination under drought stress condition is varying in varieties. The previous research result showed that the differences in germination response under drought stress can be used as early test for screening to drought tolerance in plants. The objectives of this experiment were to evaluate the germination response of 36 soybean varieties under drought stress simulated by polyethylene glycol (PEG), to know the drought-stress tolerance level of 36 soybean varieties based on germination response in medium containing PEG, and to identify drought tolerant varieties. Soybean seeds were germinated in sand medium containing several PEG (6000) at concentration 0%, 15% and 20% which equivalent to 0, -0,41 and -0,67 MPa during 5 days. Germination responses were observed by calculating vigor index, germination percentage, lateral root number and measuring hypocotyl and root lenght and seedling dry weight. The level of drought stress tolerance of soybean varieties were evaluated based on index of reduction and drought sensitivity on germination variables in stres and non-stres conditions. The research result showed that drought stress on germination media simulated by PEG decreased vigor index, germination percentage, lateral root number, hypocotyl and root lengths and dry weight of seedling. The inhibition of germination increased with reduction of water potential. The water potential -0,41 MPa inhibited vigor index and hypocotyls length in all tested varieties, but inhibited germination percentage, lateral root number and dry weight of seedling in some varieties. However, decreasing of water potential -0,67 MPa inhibited almost germination variables in all varieties, except root length. Each tested soybean variety showed differences of germination response to drought stres. Varieties of Dieng, Tidar and Sibayak showed less inhibition than others, but Anjasmoro, Burangrang, Galunggung, Kipas Putih and Tambora showed more inhibition in seedling growth. Based on index of reduction and drought sensitivity on germination variables, Dieng and Tidar were identified as tolerant varieties, while sixteen varieties as medium tolerant and seventeen varieties as sensitive ones.